2013
DOI: 10.1089/jpm.2013.0041
|View full text |Cite
|
Sign up to set email alerts
|

Using Medical Words with Family Caregivers

Abstract: The propensity to use medical words during clinical communication with family caregivers is cautioned. In order to recognize the caregiver as a contributing team member, clinicians should limit the use of medical words, provide lay explanation alongside medical terminology, and use questions to check for understanding. More research is needed to determine assessment tools to capture the caregiver's level of understanding of medication and pain management protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Health‐care professionals need to be able to assess this and tailor their use of terminology to the individual patient. Like Wittenberg‐Lyles et al . and Dahm, we suggest an adaptive approach, where patients’ needs and abilities are established and addressed in a patient‐centred way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health‐care professionals need to be able to assess this and tailor their use of terminology to the individual patient. Like Wittenberg‐Lyles et al . and Dahm, we suggest an adaptive approach, where patients’ needs and abilities are established and addressed in a patient‐centred way.…”
Section: Discussionmentioning
confidence: 99%
“…Health-care professionals need to be able to assess this and tailor their use of terminology to the individual patient. Like Wittenberg-Lyles et al 58 and Dahm, 1 we suggest an adaptive approach, where patients' needs and abilities are established and addressed in a patient-centred way. Appropriate pitching of terms can avoid the potentially damaging effects of poor communication brought about by inappropriate (too complex or too simple) use of terms.…”
Section: Discussionmentioning
confidence: 99%
“…Several substudy analyses that were related to this study but had unique research questions are reported elsewhere. 20,[23][24][25][26][27][28][29][30][31][32][33][34] Our protocol required coders to achieve intercoder agreement of 80% or greater before independently coding data. Trustworthiness in analysis was assured through prolonged engagement, an extensive audit trail, multiple coders, and regular debriefing between all researchers.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…One finding from this work was that as the grade-level talk in the conversation increased, so too did the anxiety level of caregivers (Wittenberg-Lyles et al, 2013a), which in turn led to confusion among caregivers about how to properly provide pain medication at home. Another finding was that hospice team members used six times as many medical words as caregivers (Wittenberg-Lyles et al, 2013b). "Yes, we do have caregivers who can learn how to present to an attending physician, but those are few and far between in our family caregiver population," said Wittenberg.…”
Section: Nurse Trainingmentioning
confidence: 99%